Disordered T-Cell Development and T-Cell Malignancies in SCL LMO1 Double-Transgenic Mice: Parallels with E2A-Deficient Mice - Chervinsky, David S. (American Society for Microbiology, 1999)
The gene most commonly activated by chromosomal rearrangements in patients with T-cell acute lymphoblastic leukemia (T-ALL) is SCL/tal. In collaboration with LMO1 or LMO2, the thymic expression of SCL/tal leads to T-ALL at a young age with a high degree of penetrance in transgenic mice. We now show that SCL LMO1 double-transgenic mice display thymocyte developmental abnormalities in terms of proliferation, apoptosis, clonality, and immunophenotype prior to the onset of a frank malignancy. At 4 weeks of age, thymocytes from SCL LMO1 mice show 70% fewer total thymocytes, with increased rates of both proliferation and apoptosis, than control thymocytes. At this age, a clonal population of thymocytes begins to populate the thymus, as evidenced by oligoclonal T-cell-receptor gene rearrangements. Also, there is a dramatic increase in immature CD44(+) CD25(−) cells, a decrease in the more mature CD4(+) CD8(+) cells, and development of an abnormal CD44(+) CD8(+) population. An identical pattern of premalignant changes is seen with either a full-length SCL protein or an amino-terminal truncated protein which lacks the SCL transactivation domain, demonstrating that the amino-terminal portion of SCL is not important for leukemogenesis. Lastly, we show that the T-ALL which develop in the SCL LMO1 mice are strikingly similar to those which develop in E2A null mice, supporting the hypothesis that SCL exerts its oncogenic action through a functional inactivation of E proteins.